Pengaruh Kualitas Produk Terhadap Minat Beli Smartphone Apple di Universitas Pamulang - Asep Pebirusdiana Gumilar; Nurlaili Putri Sabila; Rafly Rahim (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
The purpose of this research is to test whether product quality can influence the purchase intentions of students who use Apple smartphones at Pamulang University. The population of this study were students who used Apple smartphones at Pamulang University. Data was collected using a questionnaire distributed using purposive sampling techniques. A total of 201 respondents participated in this research. Before being analyzed using simple linear regression, the data was first tested for validity and reliability. The research results showed that all statement items in the questionnaire passed the validity and reliability tests so that further analysis could be carried out. Partial test results found that product quality had a positive and significant effect on interest in buying Apple iPhone smartphones among students at Pamulang University. Furthermore, it was found that the product quality variable influenced purchase intention by 58.7%, while the remaining 41.3% was influenced by other variables not studied.